Investigation Into the Education at Communication Faculties in Turkey - Ozupek, M. Nejat; Ozer, Deniz (Elsevier Science Bv, 2015)
The communication faculties in Turkey have become growingly popular over the last years. Meanwhile, there has been a parallel growth in the number of faculties and graduates. This being the case, a common concern has emerged to question the qualifications of incumbent instructors along with the quality of the education they provide. The present study aims to investigate the problems underlying the communication education through an academic perspective. This study tends to be a unique analysis in that it not only refers to previous studies but also brings together the common views of the academicians delivering communication education. Moreover, the study comes up with several solution proposals, deriving from the academic perspectives on these problems. (C) 2015 The Authors. Published by Elsevier Ltd.
Proceedings of 6th World Conference on Educational Sciences -- FEB 06-09, 2014 -- Grand Hotel Excelsior Convention Center, Valletta, MALTA
Keywords: Communication; communication education; communication education problems in Turkey